Properties of Whistler Mode Waves in Earth's Plasmasphere and Plumes. Issue 2 (13th February 2019) - Shi, Run; Li, Wen; Ma, Qianli; Green, Alex; Kletzing, Craig A.; Kurth, William S.; Hospodarsky, George B.; Claudepierre, Seth G.; Spence, Harlan E.; Reeves, Geoff D.
Abstract: Whistler mode wave properties inside the plasmasphere and plumes are systematically investigated using 5‐year data from Van Allen Probes. The occurrence and intensity of whistler mode waves in the plasmasphere and plumes exhibit dependences on magnetic local time, L, and AE . Based on the dependence of the wave normal angle and Poynting flux direction on L shell and normalized wave frequency to electron cyclotron frequency ( f ce ), whistler mode waves are categorized into four types. Type I: 0.5 f ce with oblique wave normal angles mostly in plumes; Type II: 0.01–0.5 f ce with small wave normal angles in the outer plasmasphere or inside plumes; Type III: <0.01 f ce with oblique wave normal angles mostly within the plasmasphere or plumes; Type IV: 0.05–0.5 f ce with oblique wave normal angles deep inside the plasmasphere. The Poynting fluxes of Type I and II waves are mostly directed away from the equator, suggesting local amplification, whereas the Poynting fluxes of Type III and IV are directed either away from or toward the equator, and may originate from other source regions. Whistler mode waves in plumes have relatively small wave normal angles with Poynting flux mostly directed away from the equator and are associated with high electron fluxes from 30 keV to hundreds of keV, all of which support local amplification. Whistler mode wave amplitudes in plumes can be stronger than typical plasmaspheric hiss, particularly during active times. Our results provide critical insights into understanding whistler mode wave generation inside the plasmasphere and plumes. Key Points: Whistler mode waves are statistically analyzed both inside the plasmasphere and in the plumes based on Van Allen Probes observations The occurrence rate and amplitudes of whistler mode waves inside the plasmasphere and plumes show dependence on L, MLT, and geomagnetic activity The majority of whistler mode waves in plumes are suggested to be locally amplified due to energetic electron injection